Reactions of large tetraaza-N,N′-dihydroacenes: formation of unexpected adducts and an unstable tetraazahexacene - Engelhart, Jens U.; Lindner, Benjamin; Tverskoy, Olena; Schaffroth, Manuel; Rominger, Frank; Bunz, Uwe H. F. (The journal of organic chemistry, 2013)
We report the reaction of several N,N′-dihydrotetraazaacenes with oxalylic chloride to give unusual adducts, which were characterized by single-crystal X-ray structures.